46,XY Sex Development Defect due to a Novel Homozygous (Splice Site) c.673_1G>C Variation in the HSD17B3 Gene: Case Report - Nurdan Çiftci; Leman Kayaş; Emine Çamtosun; Ayşehan Akıncı (Galenos Yayincilik, 2022)
The enzyme 17-β-hydroxysteroid dehydrogenase type 3 (17β-HSD3) catalyzes the biosynthesis of testosterone (T) from Δ4-androstenedione, and plays an important role in the final steps of androgen synthesis. 17β-HSD3 deficiency originates from mutations in the HSD17B gene, causing an autosomal recessive 46,XY sex developmental disorder (DSD). Patients with 46,XY karyotype can exhibit a wide phenotypic spectrum, varying from complete external female genitalia to male genitalia with hypospadias. Here we report a case of 17β-HSD3 deficiency diagnosed in the infantile period who was later found to have a novel HSD17B3 gene variation. The 14-month old patient, who exhibited a female phenotype, presented with a bilateral lump in the inguinal area. Imaging revealed bilateral testicular gonads in the inguinal area. Hormonal evaluation showed low levels of basal and stimulated serum T, a high level of androstenedione (A), and a low T/A ratio. Chromosomal analysis showed 46,XY karyotype. Sequence analysis of the HSD17B3 gene revealed a c.673_1G>C homozygous class 2 (splice site) variation in intron 9. The consanguineous parents were sequenced, and both were heterozygous for the same mutation. This variation has not been previously reported in the literature. In conclusion, a 46,XY DSD should be considered in patients with a female phenotype who exhibit gonad(s) in the inguinal area at an early age. Furthermore, in patients with insufficient T synthesis and high levels of androstenedione, 17β-HSD3 should be considered, and molecular analysis should be done for a definitive diagnosis and subsequent genetic counseling.